English Major Students’ Challenges in Acquiring Translation Skills from the Grammatical Perspective - Nguyen Thi Huong, Lan (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
Translation is a crucial ability for those pursuing linguistics, especially in relation to English. The swift advancement of 4.0 technology and the proliferation of various artificial intelligence apps have conferred signigicant benefits upon language learners. Translation encompasses more than only changing a sentence from one language to another; it involves effectively conveying the speaker’s point to the listener. Consequently, the barriers encountered by learners, alongside elements pertaining to vocabular, semantics, and culture which is considered as the initial obstacle faced by translation learners is the gramatical disparity between the source language (SL) and the target language (TL). This study utilizes a mixed-method approach, integrating the quantitative method via a mini test and survey and the qualitative method through semi-structured interviews, to identify the types and frequency of grammatical errors commonly made by Vietnamese translation learners; to comprehend learners’s perceptions regarding the significance of grammar in translation; and to investigate the grammatical challenges faced by translation learners. The research findings indicate that learners acknowledge the importance of grammar and the grammatical obstacles to producing a natural translation, as well as the prevalence of specific types of grammatical errors occurring more often in Vietnamese – the learners’ first language (L1) and English (L2) translaitons compared to L2 to L1 translations.